PENGARUH PEMBERIAN MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA HOTEL DYAN GRAHA PEKANBARU) - Talenta Novita Simanjuntak; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the provision of motivation and organizational commitment and its effect on employee performance at Hotel Dyan Graha Pekanbaru. Provision of motivation as a variable (X1), Organizational Commitment as Variable (X2), and employee performance as a variable (Y). The method in this research is descriptive and quantitative by using program of SPSS 21, where sample used is 56 employees conducted by census and technique of collecting data through questioner. The results of analysis using the validity test, test reliability, test determination, simple linear regression test, multiple linear regression test, t test and F test. So it can be concluded that the provision of motivation significantly influence employee performance at Hotel Dyan Graha Pekanbaru, Employee performance at Hotel Dyan Graha Pekanbaru, and giving motivation and organizational commitment have a significant effect on employee performance at Hotel Dyan Graha Pekanbaru.Keywords: Giving Motivation, Organizational Commitment, and Employee Performance